2001
DOI: 10.1086/318240
|View full text |Cite
|
Sign up to set email alerts
|

Iron Abundance Profiles of 12 Clusters of Galaxies Observed withBeppoSAX

Abstract: We have derived azimuthally averaged radial iron-abundance proÐles of the X-ray gas contained within 12 clusters of galaxies with redshift 0.03 ¹ z ¹ 0.2 observed with BeppoSAX. We Ðnd evidence for a negative metal-abundance gradient in most of the clusters, particularly signiÐcant in clusters that possess cooling Ñows. The composite proÐle from the 12 clusters resembles that of cluster simulations of Metzler & Evrard. This abundance gradient could be the result of the spatial distribution of gas-losing galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
(48 reference statements)
2
31
0
Order By: Relevance
“…Gradients in the iron abundance have been detected with ASCA data (Finoguenov et al 2000(Finoguenov et al , 2001White 2000), and confirmed by BeppoSax data (Irwin & Bregman 2001;De Grandi & Molendi 2001); in particular, sharp metallicity peaks in the central region seem to be typical of cooling flows/cD clusters (Fukazawa et al 2000;Irwin & Bregman 2001;De Grandi & Molendi 2001). [α/Fe] ratios also seem to display a composite behaviour, increasing with cluster radius from ∼solar in the central regions to supersolar, typical type II supernova (SN), values in the outer regions (Finoguenov et al 2000).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Gradients in the iron abundance have been detected with ASCA data (Finoguenov et al 2000(Finoguenov et al , 2001White 2000), and confirmed by BeppoSax data (Irwin & Bregman 2001;De Grandi & Molendi 2001); in particular, sharp metallicity peaks in the central region seem to be typical of cooling flows/cD clusters (Fukazawa et al 2000;Irwin & Bregman 2001;De Grandi & Molendi 2001). [α/Fe] ratios also seem to display a composite behaviour, increasing with cluster radius from ∼solar in the central regions to supersolar, typical type II supernova (SN), values in the outer regions (Finoguenov et al 2000).…”
Section: Introductionmentioning
confidence: 59%
“…Metallicities are in fact typically measured at most within half of the virial radius (Finoguenov et al 2000(Finoguenov et al , 2001De Grandi & Molendi 2001;Irwin & Bregman 2001); measurements hardly reach r 500 , which is typically 63% of r 200 , and in terms of cluster mass M 500 ∼ 0.63 M 200 as well (see Reiprich & Böhringer 2002) 1 . For the sake of the chemical enrichment what matters is the mass averaged metallicity, obtained by convolving metallicity distributions with gas profiles within the same radius, and the IMLR should also be evaluated from the gas, metals and galactic luminosity within the same radius (as in Finoguenov et al 2000Finoguenov et al , 2001Finoguenov et al , 2003.…”
Section: M/l Ratio and Imlr Of Galaxies: Pnj Vs Salpetermentioning
confidence: 99%
“…Future X-ray Tozzi et al (2003). For comparison, the low redshift samples from Mushotzky & Loewenstein (1997), and Irwin & Bregman (2001) are also plotted.…”
Section: Dynamical State Of the Clustermentioning
confidence: 99%
“…Gas dynamic stripping may be related to the chemical enrichment of the ICM, and possibly also its dynamics (Deiss & Just 1996). A preliminary conclusion from the analysis of X‐ray spectra of the ICM is that the metal abundances in the ICM vary from one type of cluster to another, and that the distribution of metals within clusters, especially ‘cooling flow’ clusters, can be non‐uniform (Finoguenov, David & Ponman 1999; Irwin & Bregman 2001; De Grandi & Molendi 2001). This suggests that both winds (mainly responsible for [Si] enrichment) and galaxy stripping (resulting mainly in [Fe] enrichment) contribute to the chemical enrichment of the ICM to variable extents, possibly according to the structure of the cluster and the age of the brightest cluster galaxies.…”
Section: Introductionmentioning
confidence: 99%